Evaluasi Kinerja Bright PLN Dalam Menanggapi Keluhan Pelanggan Di Kota Batam - Jayanti Wanda Anazatri; Jamhur Poti; Chaerey Ranba Sholeh (Jurnal Relasi Publik, 2023)
The phenomenon of the problem in this research is that the complaints that are often reported by customers are related to sudden blackouts for hours, the most complaints are also followed by APP/KWH meter disturbances which are usually caused by the PLN server having an error or problem.The purpose of this study was to analyze the performance of bright PLN in responding to complaints in Batam City, to find out what PLN customer complaints were, to find out customer satisfaction related to bright PLN's performance. The approach used in this research is descriptive and qualitative research. A qualitative approach is a research technique that produces descriptive data in the form of written/oral words about individuals or observed behavior. This approach aims holistically on the background and the individual. Qualitative descriptive research is to describe the informants' opinions as they are in accordance with the research questions. The focus in this study, the authors put more emphasis on one main indicator to assess the performance of Bright PLN Batam City employees. The indicator is Responsiveness. Data collection techniques in this study were interviews, observation, documentation review. Informants in this study amounted to 14 people.